A review of Vellozo’s names for Polygalaceae in his Flora Fluminensis - Pastore, José Floriano B. (Phytotaxa, 2013)
Names of Polygalaceae used by Vellozo in his Flora Fluminensis are reviewed within the current floristic context of the State of Rio de Janeiro and its bordering areas, as well as the morphological evidence provided. Nearly all of Vellozo’s names are placed as synonyms of older names, except for a new combination for Polygala disperma as Bredemeyera and Polygala appendiculata which is considered a valid name for P. leptocaulis. All names not yet typified are here lectotypified, except for B. autranii.